Long-distance spin-transport across the Morin phase transition up to room temperature in ultra-low damping single crystals of the antiferromagnet α-Fe2O3 - Lebrun, Romain; Ross, Andrew; Gomonay, Olena; Baltz, Vincent; Ebels, U.; Barra, A. -L.; Qaiumzadeh, A.; Brataas, A.; Sinova, Jairo; Klaeui, M. (Nature Communications, 2020)
Antiferromagnetic materials can host spin-waves with polarizations ranging from circular to linear depending on their magnetic anisotropies. Until now, only easy-axis anisotropy antiferromagnets with circularly polarized spin-waves were reported to carry spin-information over long distances of micrometers. In this article, we report long-distance spin-transport in the easy-plane canted antiferromagnetic phase of hematite and at room temperature, where the linearly polarized magnons are not intuitively expected to carry spin. We demonstrate that the spin-transport signal decreases continuously through the easy-axis to easy-plane Morin transition, and persists in the easy-plane phase through current induced pairs of linearly polarized magnons with dephasing lengths in the micrometer range. We explain the long transport distance as a result of the low magnetic damping, which we measure to be ≤ 10−5 as in the best ferromagnets. All of this together demonstrates that long-distance transport can be achieved across a range of anisotropies and temperatures, up to room temperature, highlighting the promising potential of this insulating antiferromagnet for magnon-based devices.
CRIS-Team Scopus Importer:2023-03-27